Integrating Hydroponic Urban Farming to Improve Food Sustainbility in Islamic Boarding Schools, Tasikmalaya - Qoriah, Qoriah; Taufik, Muhamad; Purwanto, Yedi; Saepudin, Epin; Hidayat, Fandi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Food security has increasingly become a crucial issue in Indonesia, especially amid climate change, urbanization, and population growth. The government’s free nutritious lunch program further emphasizes the need for healthy and sustainable food availability. However, various challenges remain, such as limited productive land, the conversion of agricultural land, and the high dependency on food imports. This community engagement program is designed through a literature study that explores the potential of applying hydroponic-based urban farming technology in Suryalaya Islamic Boarding School, Tasikmalaya. The novelty of this program lies in integrating food security concepts with the pesantren environment, which has rarely been addressed by modern agricultural innovations. Pesantren are considered strategic, as they serve not only as educational centers but also as broad-based communities capable of fostering food self-sufficiency. Through education and training grounded in literature-based studies, this program is expected to enhance the skills of students and teachers in managing sustainable cultivation, while also providing a pilot model for other Islamic boarding schools in Indonesia